The Streptokinase Reactivity Test. I. Standardization - Amery, A; Maes, H; Vermylen, J; Verstraete, M (Thrombosis and Haemostasis, 1963)
1. An attempt was made to standardize a method which determines the reactivity of a given blood sample with streptokinase (SKRT).2. The nature of the thrombin and streptokinase used can greatly influence the test.3. The 20 minutes value is less influenced by a number of parameters than other points on the streptokinase versus lysis time plot.